Epigenetic Markers of Renal Function in African Americans. (12th December 2013) - Bomotti, Samantha M.; Smith, Jennifer A.; Zagel, Alicia L.; Taylor, Jacquelyn Y.; Turner, Stephen T.; Kardia, Sharon L. R.
Abstract : Chronic kidney disease (CKD) is an increasing concern in the United States due to its rapidly rising prevalence, particularly among African Americans. Epigenetic DNA methylation markers are becoming important biomarkers of chronic diseases such as CKD. To better understand how these methylation markers play a role in kidney function, we measured 26, 428 DNA methylation sites in 972 African Americans from the Genetic Epidemiology Network of Arteriopathy (GENOA) study. We then evaluated (1) whether epigenetic markers are associated with estimated glomerular filtration rate (eGFR), (2) whether the significantly associated markers are also associated with traditional risk factors and/or novel biomarkers for eGFR, and (3) how much additional variation in eGFR is explained by epigenetic markers beyond established risk factors and biomarkers. The majority of methylation markers most significantly associated with eGFR (24 out of the top 30) appeared to function, at least in part, through pathways related to aging, inflammation, or cholesterol. However, six epigenetic markers were still able to significantly predict eGFR after adjustment for other risk factors. This work shows that epigenetic markers may offer valuable new insight into the complex pathophysiology of CKD in African Americans.